Assessment on the Gulayan sa Barangay in Davao City an urban farming program - Millendez, Bert James C.
With the Philippine's increasing population and weakening agricultural sector, it would be hard for the country in the long term to provide food security for the people, especially in supplying and satisfying their demand for vegetables. One solution to this is urban farming, which is the growing of plants and the raising of animals within and around cities (Ruaf Foundation, n.d.). Urban farming occurs within and surrounding the boundaries of cities throughout the world and includes products from crop and livestock agriculture, fisheries and forestry. (FAO, 2010). One example of urban farming here in the Philippines is the Gulayan sa Barangay in Davao City. The Gulayan sa Barangay (GSB) was originally part of the project of the Vegetable Industry Council of Southern Mindanao, Inc. (VICSMIN) called ?Vegetable Awareness and Appreciation Campaign?. This project was conducted in cooperation with the Department of Agriculture. Each Barangay is encouraged to put up a vegetable garden and landscape the area using different vegetables and ornamental plants. This study is about the assessment on the of the Gulayan sa Barangay in Davao City. The results were: first, the Gulayan sa Barangay can add to almost 24,000 kgs of vegetable supply locally. Next, in terms of price, GSB is cheaper than those from Matina Market and Bankerohan Bagsakan. GSB can supply nutritious, healthy and accessible food since they are producing vegetables without synthetic fertilizers added. Lastly, it is highly recommended to replicate the Gulayan sa Barangay program in other barangays in the city and later on in other cities in the country.